Information gain in the brain's resting state: A new perspective on autism - Pérez Velázquez, José Luis; Galán, Roberto F. (Frontiers in Neuroinformatics, 2013)
Along with the study of brain activity evoked by external stimuli, an increased interest in the research of background, “noisy” brain activity is fast developing in current neuroscience. It is becoming apparent that this “resting-state” activity is a major factor determining other, more particular, responses to stimuli and hence it can be argued that background activity carries important information used by the nervous systems for adaptive behaviors. In this context, we investigated the generation of information in ongoing brain activity recorded with magnetoencephalography (MEG) in children with autism spectrum disorder (ASD) and non-autistic children. Using a stochastic dynamical model of brain dynamics, we are able to resolve not only the deterministic interactions between brain regions, i.e. the brain’s functional connectivity, but also the stochastic inputs to the brain in the resting state; an important component of large-scale neural dynamics that no other method can resolve to date. We then computed the Kullback-Leibler divergence, also known as information gain or relative entropy, between the stochastic inputs and the brain activity at different locations (outputs) in children with ASD compared to controls. The divergence between the input noise and the brain’s ongoing activity extracted from our stochastic model was significantly higher in autistic relative to non-autistic children. This suggests that more information is produced in the brains of subjects with autism at rest. We propose that the excessive production of information in the absence of relevant sensory stimuli or attention to external cues underlies the cognitive differences between individuals with and without autism. We conclude that the information gain in the brain’s resting state provides quantitative evidence for perhaps the most typical characteristic in autism: withdrawal into one's inner world.